Virtual enterprise in SME networks - Esposito, Emilio; Evangelista, Pietro; Lauro, Vincenzo; Raffa, Mario (Piccola Impresa / Small Business, 2009)
Small and medium sized enterprises (SMEs) operating in industrial districts havehistorically provided an important alternative to the advantages achieved through alarger production scale in the context of the Italian industrial system. However, in recentdecades uniform growth in SME networks has come to an end. The industrial districtmodel has often proved to be rather a ‘stage’ in one of the possible different paths ofindustrialisation. In fact, small firms are evolving towards a scenario characterised byincreasing competition and massive introduction of ICT. These changes have acceleratedthe search for new organisational forms that allow SMEs facing the growing complexityof the business environment. Furthermore, it is of paramount importance to sustain local SME networks especially during period of economic crisis. One possible way may be tosupport the virtualisation potential of SME networks and encourage their rapid evolutiontoward the Virtual Enterprise (VE) model order to seize new development opportunities.Despite increasing academic interest toward the VE, there are a number of key issues notaddressed by the current literature such as the possible form VEs may assume and the lackof empirical investigations. This paper tries to fill these voids. Two are the main objectivesof this paper. Firstly, to analyse the possible models that VE may assume when participatedby SMEs and, secondly, to fill the existing empirical research gap in this field. In order toachieve the above objectives a comprehensive literature review on the subject has been firstcarried out. Subsequently, an exploratory questionnaire survey has been implemented ina SME network located in the eastern area of Naples city. The literature review allows theidentification of two extreme VE forms: the Hierarchical and the Holarchical models. Theresult of the questionnaire survey suggests that the network analysed may be a potentialpool of VEs in which temporary relationships oriented to specific projects are continuouslyformed and reformed. Finally, the comparison between literature review and surveyfindings allows establishing that VEs created in that network may assume a hybrid formbetween the two extreme models identified.